Project-Based Learning in Developing English Language Skills and 21st Century Skills: Students’ Voices in Academic Writing Course - Panggih Rahardi; Reyhan Hernanda; Ega Bagus Panuntun; Lilia Indriani; Atsani Wulansari (Metathesis: Journal of English Language, Literature, and Teaching, 2023)
Project-based learning (PBL) is one of the teaching strategies that has become significant in the twenty-first century. English has also become an important language that needs to be mastered nowadays. Therefore, this research was done to find out how the students felt about the use of project-based learning in academic writing course in developing their English language skills and 21st century skills. The issues experienced by students in project-based learning implementation are also revealed in this study. By employing a qualitative research approach, this study invited 40 English-major undergraduate students from a state university in Central Java, Indonesia, who are currently taking their academic writing course. Students in this course must work collaboratively to complete their research projects and produce scientific papers that will eventually be published. This study's findings successfully demonstrated the students' voices that they believe project-based learning has improved their English and 21st century skills. Writing, problem-solving, and critical thinking are the three skills with the highest proportion in this study. Additionally, the issues with the implementation of project-based learning in academic writing course include student motivation, time management, teaching-learning process, and students' teamwork.